2015
DOI: 10.1097/rli.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure of Digital Breast Tomosynthesis Using an Antiscatter Grid Compared With Full-Field Digital Mammography

Abstract: The radiation dose of patients undergoing a single-view DBT was comparable to a single-view FFDM. For patients with thicker breasts, the radiation dose of DBT was slightly lower than FFDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A previously published research paper 10 concluded that the translation of this technology may impact clinically by early detection of a breast lesion and further improvement in patient management, whether used for screening or diagnostic purposes. However, limited work has been published on radiation doses from DBT or a combination of DBT and FFDM for a range of clinically relevant mammographic parameters 11–14 . A precise comparison of dose levels between FFDM and DBT, based on clinical data, is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A previously published research paper 10 concluded that the translation of this technology may impact clinically by early detection of a breast lesion and further improvement in patient management, whether used for screening or diagnostic purposes. However, limited work has been published on radiation doses from DBT or a combination of DBT and FFDM for a range of clinically relevant mammographic parameters 11–14 . A precise comparison of dose levels between FFDM and DBT, based on clinical data, is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been seen that by itself, the dose of DBT is comparable to Full Field Digital Mammography (FFDM), and may even be lower in thick breasts. [ 29 ] Our study, however, shows that DBT is most useful in this population due to the higher density of breasts in younger patients. The average age of patients with ACR density 3 and 4 breasts (where DBT was found most useful) were 43 and 36, respectively, showing that it may be particularly valuable in women below 45 years of age.…”
Section: Discussionmentioning
confidence: 72%
“…115 Several groups are addressing these issues with new systems that can perform whole-breast μCT; 50,60,62 however, they impart radiation dose 2× to 3× that produced from clinical mammography or digital breast tomosynthesis systems. 60,116 Thus, preclinical and clinical μCT may both prove valuable tools for future QMIB studies.…”
Section: Microcomputed Tomographymentioning
confidence: 99%